Separation and Characterization of Heterogeneity Among Various Sizes of Outer Membrane Vesicles Derived from the Probiotic Escherichia coli Nissle 1917 - Ning Li; Hongbo Xin; Keyu Deng (Membranes)
Outer membrane vesicles (OMVs) are extracellular vesicles secreted by Gram-negative bacteria with diameters of 20–250 nm. OMVs contain various biologically active substances from their parent bacteria, such as proteins, lipids, and nucleic acids. Escherichia coli Nissle 1917 (EcN) is a Gram-negative probiotic that resides in the human intestine. EcN-derived OMVs are pivotal in modulating intestinal immune responses. However, few studies have addressed the heterogeneity of EcN-derived OMVs in terms of size, significantly limiting the research on their clinical applications. Currently, there are a lack of feasible methods for obtaining EcN-derived OMVs of different sizes. To address this knowledge gap, we developed a membrane filtration method to isolate EcN-derived OMVs of varying sizes. In this study, we first used gradient filtration to isolate high-purity EcN-derived OMVs and conducted a proteomic analysis. Subsequently, we used membrane filtration to separate the EcN-derived OMVs by size. We successfully obtained EcN-derived OMVs of three specific sizes: <50 nm, 50–100 nm, and 100–300 nm. We then performed proteomic analyses of these EcN-derived OMVs and compared their protein profiles. Finally, we compared the ability of each EcN-derived OMV type to induce RAW264.7 macrophages to secrete the pro-inflammatory factor interleukin (IL)-1β and the anti-inflammatory factor IL-10. The EcN-derived OMVs contained 646 different proteins overall; those of different sizes contained different protein types. Among them, the EcN-derived OMVs in the <50 nm group contained significantly fewer proteins (262 different types in total) than those in the 50–100 nm (1603 types) and 100–300 nm (1568 types) groups. Furthermore, the <50 nm group had fewer membrane proteins (40) than the 50–100 nm (215) and 100–300 nm (209) groups. We also found that RAW264.7 macrophages secreted different concentrations of IL-1β and IL-10 following co-incubation with the three EcN-derived OMV types. The 50–100 nm EcN-derived OMV group showed a stronger effect in terms of inducing inflammatory cytokine secretion compared to the other two groups. This study provides direct experimental evidence that EcN-derived OMVs of different sizes exhibit heterogeneous properties.